THEORETICAL BASIS OF FORMATION OF PERSONNEL DEVELOPMENT SYSTEM - Жеребило, Ірина; Лаврів, Христина (Socio-economic relations in the digital society, 2019)
The article is devoted to the research of the problem of human resource management system. It is discovered the essence of the system, its types and directions . The relationships between the Human Resource system and the company management strategy are explained. It has been determined that the personal development was studied from the two points of view — individual and organizational, which positions analyze the complex socio-economic phenomenon. It has been found that solving fo practical issues related to personnal development requires theoretical study in the field. Personal development is ensured by activities related to staff evaluation with the purpose of manufacturing adaptation and staff appraisal, employee career planning, and staff development incentives. The constituent processes of development of the personnel organization are revealed. The subject and object of the personnel development system are identified. The advantages of personnal development system in the organization were identified. Integral management of personnel development represents the development and implementation of measures that are aimed to improve the qualitative characteristics of employees (skills, knowledge, motivation, competencies, etc.). The study also outlines the structure of personnel development goals and objectives. It has been found out that the purpose of staff development is to increase its intellectual potential through investment in human capital. And the levels of definition of human capital are revealed. The relationship between the personal development system and the company management strategy is analyzed. Thus, it was found that each variant of the organization’s management strategy defines specific variant of the staff development strategy.